Patient's Delay in Medical Treatment and Treatment Seeking Behavior among Tuberculosis Patients in Phrasamut Jaedee Sawattayanon Hospital, SamutPrakan Province - คูศิริวิเชียร, ทิพวรรณ (Disease Control Journal, 2007)
Delayed initiation of treatment among tuberculosis patients was a common problem which might contribute to the high burden of tuberculosis in community. The objectives of this study were to access patient delays and factors of reasons for patients delay and to describe the treatment seeking behavior among tuberculosis patients, by a Hospital-based cross-sectional study design. The result of this study found that, there were 76 cases of tuberculosis patients, 57 cases (75.0%) were delayed more than 3 weeks before seeking treatment. Patients delay was significantly higher among patients who did not suspect that they might have TB (Adjusted OR=2.7, 95%CI = 1.91-9.73, p-value=.005), among those who treated with self-medication (Adjusted OR=3.83, 95%CI = 5.48-13.21, p-value<.001) and among those who thought their illness was not serious (Adjusted OR=4.8, 95%CI = 1.95-10.28,p-value=.002). In conclusion: this unacceptably long patient delay called for identification and inclusion of feasible strategies to promote TB awareness in community and promote early treatment in the National Tuberculosis Control Programme.